The Effect of Education and Implementation of Evidence-Based Nursing Guidelines on Infants’ Weight Gaining in NICU - Salehi, Zahra (Glob J Health Sci, 2015)
BACKGROUND: Educating evidence-based guidelines influences increased quality of nursing cares effectively. Infant’s weight gaining is one of the most important indicators for measuring quality of nursing care in NICU. The research is conducted with the aim of surveying the effect of education and implementation of educating evidence-based guidelines on infants’ weight gaining in NICU. METHODS: This two-group clinical trial study was conducted in 2013 on one hundred infants in Baqiyatallah (AJ) hospital of Tehran. It was performed by using non-probable and convenient sampling. Data collection tools included; infants’ demographic questionnaire and a researcher-made checklist to record infants’ weight by using a weighing scale. Infants’ weight was recorded before intervention and two months after implementation of the guidelines, then data were analyzed by using SPSS19 statistical software. FINDINGS: Mean weight of the infants in the control group on admission and on discharge was respectively; 1771(41.71) and 1712(42.68), and mean weight of the infants in intervention group on admission and on discharge was respectively; 1697(37.63) and 1793(40.71). After two months, infants’ weight gaining in intervention group was more than control group and it was statistically significant (P = 0.001). CONCLUSION: Results of the present study showed that implementation of evidence-based instruction an effective and economical method regarding infants’ weight gaining. Therefore it is recommended to the authorities and managers of the hospitals and educational centers of the healthcare services to put education and implementation of educating evidence-based instruction the priority of their work plans.